Tradisi Bapukung pada Masyarakat Suku Banjar dan Pengaruhnya terhadap Pertumbuhan Anak di Desa Ujung Purui Kabupaten Tabalong - Najwa, Nur; Hidayah, Nor; Andini, Najwa Femilia; Prastricia, Meily Andini; Hasanah, Nur; Putri, Andini Octaviana (Universitas Nurul Jadid, 2024)
Traditions are culturally ingrained practices passed down through generations, reflecting noble values. The Banjar tribe in South Kalimantan upholds the Baayun Bapukung tradition, a childcare practice involving placing infants in a sitting position wrapped in cloth and gently swinging them. This study examines the Bapukung tradition's significance in Ujung Purui Village and its impact on child growth. Using a qualitative phenomenological approach, data were collected through interviews, observations, and documentation, analyzed with NVivo software, and interpreted via Max Weber's social action theory. The results indicate that the community perceives Baayun Bapukung as a beneficial tradition supporting infant health and development. Rational and value-based motives underlie the practice, aligning with Weber’s instrumental rationality. However, pediatricians highlight potential risks, advising against tight swaddling or excessive swinging due to possible respiratory and physical complications. The study emphasizes bridging traditional practices with modern medical insights to support cultural preservation and child welfare